Zarys działalności Komunalnej Kasy Oszczędności miasta Łodzi w okresie wielkiego kryzysu gospodarczego (1930–1935) - Marks, Bogusław Piotr (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2009)
The activity of the Municipal Savings Bank of the city of Łódź (MSB) in the period of the great economic crisis (1930–1935) is the object of this article. The Savings-bank began its activity on 31 October 1930 on the basis of the Polish Republic President’s order of 13 April 1927 about municipal saving-banks, and supplemented by the executive provisions of both the Minister of Internal Affairs and the Minister of Treasury on 26 March 1928. It functioned on the basis of the Bank Charter confirmed by the Provincial Governer of Łódź on 31 July 1930. It was one of the many institutions of this type acting in the Second Republic of Poland. The main reason of setting up the MSB in Łódź was to make saving easier and to protect savings against speculation and loss, and also, to make giving a “cheap” credit more available. The Savings Bank had the personality of a public institution of public character and this largely determined the aims and the principles of its functioning. In the first part of this article was introduced the outline of the development of savings banks on the Polish land during the period of the Partitions of Poland and after regaining independence by Poland (till 1935), while in the principal part were presented the legal and organizational bases of functioning of the MSB in Łódź; besides the bank’s activity concerning its passive operations (accumulating savings deposits) and the active ones (giving credits and loans) were analysed. A lot of place was dedicated to the organizational structure of the Savings Bank, and especially to the range of its powers’ operation – the Council and the Management (the Board), and also to the Auditing Committee. The city of Łódź played an immense role as a formal founder of the MSB as well as a guaranteeing association. It was the guarantor of the functioning stability of the Savings Bank. The municipal authorities made, among other things, a list of losses that were result of giving credits and loans by the Savings Bank, which borrowers were not able to pay off. Yet, it must be underlined here that the property of the Savings Bank was administered separately and legally separated from the commune property, because – having its own wealth – the Savings Bank was responsible for its liabilities with regard to its creditors. In spite of unusually difficult economic conditions in which the savings bank acted and “irresponsible actions” of the first authorities, it managed to survive the period of great economic crisis in a comparatively good economic shape. It was proved, among others, by the systematic growth of the number of passbooks as well as by the amount of the savings in them, and also – despite the break down in 1933 – by the sums of given credits and loans. MSB enjoyed a wide confidence among the local society, and especially among its “average and lower” classes which made up its basic customers.